Restructured searls family of estimators of population mean in the presence of nonresponse - Ahmadini, Abdullah Ali H.; Yadav, Taruna; Yadav, S. K.; Al Luhayb, Asamh Saleh M. (Frontiers in Applied Mathematics and Statistics, 2022)
Non-response is a major problem encountered by surveyors when conducting sampling surveys. In the present paper, we suggest a naïve modified Searls method of estimation for elevated estimation of population mean of the primary variable under investigation, utilizing the known auxiliary parameters. The bias along with the Mean Squared Error (MSE) of the introduced estimator is calculated up to the approximation of first order. Under the problem of nonresponse, the presented estimator is compared with the competing usual unbiased estimator as well as with other competing population mean estimators under the issue of nonresponse. The efficiency criteria for which the introduced estimator outperforms the estimators in competition are determined. These conditions for which the introduced estimator outperforms the estimators in competition are verified using five real data sets. The MSEs for the introduced along with the estimators in competition are calculated for the five considered populations. The estimator with the least MSE or highest Percentage Relative Efficiency (PRE) is recommended for practical exercise in different areas of applications.